1994
DOI: 10.1002/ajmg.1320510439
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis in known fragile X carriers

Abstract: Prenatal diagnosis for fragile X syndrome was performed in 34 pregnancies of 33 known carriers, on 22 chorionic villus samples (CVS), and 15 amniocentesis samples. Fetal and maternal DNA were analyzed by the EagI/EcoRI Southern blot of Rousseau et al. [1991: N Engl J Med 325:1673-1681], with detection of full mutations ensured by a second loading with brief electrophoresis. As a supplemental assay for full mutations, cytogenetic induction was performed in 20 cases. Positive cytogenetic results were helpful in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In addition, they found that the premutation carriers were well distributed among all the Jewish ethnic groups, in contrast to a previous study. 39 An Italian study of ~2,000 mothers and their newborns in the general population found a premutation carrier frequency of 1 in 109 females and 1 in 225 newborn males (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). 48 A fragile X screen of 10,000 newborn males in Taiwan showed a prevalence of 1 in 1,674.…”
Section: Fx 282: Premutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they found that the premutation carriers were well distributed among all the Jewish ethnic groups, in contrast to a previous study. 39 An Italian study of ~2,000 mothers and their newborns in the general population found a premutation carrier frequency of 1 in 109 females and 1 in 225 newborn males (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). 48 A fragile X screen of 10,000 newborn males in Taiwan showed a prevalence of 1 in 1,674.…”
Section: Fx 282: Premutationsmentioning
confidence: 99%
“…However, because it is unwarranted to use methylation status or X-inactivation for phenotypic prediction of a full mutation, the possible hypomethylation of this tissue is no disadvantage, provided that the tissue-specific basis of the hypomethylation is understood. 56,57 It is an acceptable option to omit methylation analysis entirely when testing CVS specimens. In the minor fraction of CVS cases with a result that is ambiguous between a large premutation and a small full mutation by size criteria alone, a follow-up amniocentesis may be required; • The degree of somatic variation in a full mutation "smear" has a wider range of possibilities than is typically seen in blood specimens, from very limited to extraordinarily diffuse; • Mosaicism between trophoblasts and somatic cells is theoretically possible.…”
Section: Fx 282: Premutationsmentioning
confidence: 99%
“…As the PCR methylation test is rapid and simple and requires small amounts of the patients DNA sample, we used it to perform prenatal diagnoses on DNA extracted from amniocytes or fetal blood. In chorionic villi, the methylation status is generally not completely established [Maddalena et al, 1994], and the use of chorionic villi samples for methylation analysis is still to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…The remainder of the culture was studied with fluorescence in situ hybridization (FISH). Analysis using alpha satellite X probe revealed approxi- Cytogenetic analysis of cultured chorionic villi often reveals tetraploid cells and maternal contamination is seen in 0·03-13 per cent of cultures (Ledbetter et al, 1992;Maddalena and Hicks, 1994). Therefore subsequent use of cultured cells for FISH is inappropriate.…”
Section: Misconceptions About Mosaicismmentioning
confidence: 99%